Heritability of peach tree resistance to bacterial leaf spot - Varago, André Luiz; Citadin, Idemir; Sachet, Marcos Robson; Penso, Gener Augusto; Raseira, Maria do Carmo Bassols (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the broad-sense heritability reaction to bacterial leaf spot (Xanthomonas arboricola pv. pruni), in peach tree populations obtained from directed crosses. Disease severity and defoliation of the genotypes were evaluated in field conditions, with posterior measurement of the healthy leaf area duration (HAD). The observed average heritability (0.51) indicates that the use of the evaluated genitors can be effective for the development of cultivars with higher resistance to the disease.